The impacts of cash transfers on mental health and investments: Experimental evidence from Mali - Hidrobo, Melissa; Karachiwalla, Naureen; Roy, Shalini (International Food Policy Research Institute, 2020)
Economic resilience requires future-oriented decision-making around income generation and protection in case of shocks. However, poverty is highly correlated with poor mental health, limiting forward-looking decision-making, thus perpetuating poverty. In this paper, we estimate the impacts of Mali's national cash transfer program, Filets Sociaux (Jigis-émèjiri), on measures of psychological well-being, cognition, and time preferences. We find that receiving the program improved household decision-makers' perceptions of economic and food security and reduced their self-reported anxiety. While cognitive function was not a ected, recipients of the transfers experienced greater self-esteem and a modest increase in a measure of patience. Consistent with reduced stress, higher self-esteem, and increased patience, the program also increased investments in productive assets. Results suggest that, in addition to cash transfers providing the economic resources to support investments in the future, they may also build psychological resources for supporting these investments.